Practically oriented e-learning workshop for knowledge improvement in engineering education computer control of electrical technology - Apse-Apsitis, P.; Avotins, A.; Krievs, O.; Ribickis, L. (Proceedings of the 2012 IEEE Global Engineering Education Conference (EDUCON), 2012)
Creation of good knowledge is based on practical exercise combined with theory learning. Studies in electrical engineering require many different laboratory exercises, traditionally carried out within the premises of university, where students can practice only several hours per week or even less. Such limited possibilities stipulate longer course durations and reduce knowledge creation quality. Possibility to gain some practical skills before carrying out laboratory assignments in real laboratory can become an essential part of the studies., facilitating much deeper understanding of the subject. For this reason a web-based e-Learning distance workshop in electrical engineering is elaborated and discussed in this paper. It is planned to cover courses in electrical drives, power electronics, LED lightning and automatic control.